ANALYSIS OF THE IMPLEMENTATION OF GOVERNMENT REGULATION ARTICLE 5 PMK NUMBER 20 OF 2021 CONCERNING SALES TAX ON LUXURY GOODS ON CONSUMER PURCHASING POWER DURING THE COVID-19 PANDEMIC - Amyati Amyati; Agustinus Ekensianus Parung; Ryan Fahmi (JURNAL ILMIAH EDUNOMIKA, 2022)
Trading activities of a country cannot be separated from the imposition of taxes, especially PPn and PPnBM, which are the largest income for Indonesian State treasury revenues especially coming from people who have middle and upper economies. This study aims to determine the effect of the PP Article 5 PMK policy Number 20 of 2021 on people's purchasing power during the covid -19 pandemic. The research method used is descriptive qualitative. This research was conducted at GAIKINDO (Indonesian Automotive Industry Association) by analyzing motor vehicle sales data from three brands, namely, Daihatsu, Honda and Toyota, with periods from November 2020 – to February 2021 and March 2021 – to June 2021. For the Toyota brand, there was an increase of 5,387 units or around 20.15%, for the Daihatsu Bran,d there was an increase of 2,930 units or around 29.82,% and for the Honda Brand, there was a decrease of 4,423 units or around 27.26%%, in this case,e due to a decrease in the number of production and weakening sales in the Japanese market and its exports. Based on the explanation above, it can be concluded that there increase in sales for t, the Toyota and Daihatsu brands due to the PPnBM incentive with a tariff of 100%. This also affects the purchasing power of consumers during the Covid-19 pandemic.